2020
DOI: 10.1111/pim.12792
|View full text |Cite
|
Sign up to set email alerts
|

Dicrocoelium ova can block the induction phase of experimental autoimmune encephalomyelitis

Abstract: A dramatic increase has been observed in the prevalence of autoimmune and allergy diseases in developed countries during 1980-1999. 1,2 The expansion of inflammatory diseases has coincided with the improvement of vaccination and antibiotics consumption over such a short period of time. 3 These factors decrease the natural contact of individual's immunity with infectious agents. Such agents may contribute to the development of immune system disorders as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…So far, only one study has been conducted on the protective impact of this parasite. Navi et al have reported that D.dendriticum infection with elevated IL-4 cytokines and reduced IFN-Y cytokine responses resulted in a reduction of clinical and pathological signs, as well as a delay in disease progression in the EAE model (31). Our results also emphasize the role of IL-4 in reducing in ammatory and pathological responses in DSS-induced colitis mice.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…So far, only one study has been conducted on the protective impact of this parasite. Navi et al have reported that D.dendriticum infection with elevated IL-4 cytokines and reduced IFN-Y cytokine responses resulted in a reduction of clinical and pathological signs, as well as a delay in disease progression in the EAE model (31). Our results also emphasize the role of IL-4 in reducing in ammatory and pathological responses in DSS-induced colitis mice.…”
Section: Discussionsupporting
confidence: 78%
“…Helminths or parasitic worms as the immune regulators can with skew the immune system towards Th2 and Treg responses and inhibit pro-in ammatory Th1, Th17 immune responses, and thereby reducing in ammation (12). IL4 (Th2) actively suppress Th1 pro in ammatory cells and reduce the production of TNFα and IFN-Y (13). A growing body of investigation in murine models has supports the protective roles of helminth infection and their products in modulate immune response and block ongoing in ammation (8).…”
Section: Introductionmentioning
confidence: 99%
“…Then antibiotics were removed with three sterile PBS washes. Finally, the eggs were counted with Neobar Lam and frozen at −80°C until use 23 …”
Section: Methodsmentioning
confidence: 99%